320 The Effects of the COVID-19 Pandemic on Penetrating Neurotrauma at a Level 1 Trauma Center. (1st March 2022) - Yang, George L.; Johnson, Mark D.; Solomon, Daniel; Ferguson, Andrew; Wright, James Monroe; Johnson, Reid A.; Gerges, Christina; Parr, Ann M.; Ngwenya, Laura B.
Abstract : INTRODUCTION: The COVID-19 pandemic forced the implementation of social distancing guidelines to minimize spread of the coronavirus. However, it is not yet understood what effects these precautions had on the rates of penetrating neurotrauma. METHODS: We retrospectively analyzed neurotrauma data from our institutional trauma registry from distinct periods defined as pre-COVID-19 (March 2019-September 2019) and COVID-19 (March 2020-September 2020). Demographics, injury characteristics, mechanisms of trauma, and past medical history (including psychiatric diagnosis) were collected. Data were analyzed for between-group differences and presented as odds ratios. RESULTS: We observed a significant rise in the number of neurotrauma cases in 2020 (558 vs. 630, OR 1.129 [1.0071, 1.2657]). There was a decrease in the proportion of male victims (71.3% vs. 68.6%, p = 0.03). There were significant differences noted in the mechanism of injury between groups. Patients in 2020 were less likely to present with falls (42.3% vs. 34.3%, OR 0.7119 [0.5627, 0.9005]) and more likely to present with GSW (4.48% vs. 7.78%, OR 1.7981 [1.0951, 2.9523]). Of the patients with penetrating cranial injuries, the most common motive was assault (56.7% vs. 60.0%), followed by self-inflicted (13.3% vs. 20.0%) and accidental (20.0% vs. 18.3%) with a significant difference between years (p = 0.0043). The presence of comorbid psychiatric illness or substance abuse did not confer an increased odds of presenting with penetrating injuries. No significant differences were noted in mean arrival or discharge GCS or injury severity as measured by ISS. However we did observe significant increases in patients presenting with bilaterally reactive pupils (48.3% vs 59.3%, p = 0.0025), patients discharged home (27.6% vs 37.3%, p = 0.0002), and survival at 6 months (41.4% vs. 54.2%, p = 0.0188). CONCLUSION: We observed a higher rate of penetrating neurotrauma while social distancing measures were in place. It is unclear if the psychosocial effects of quarantine and social distancing had a causative relationship with the increased rates of assault and self-inflicted penetrating injuries.